Fractal analysis of heart rate variability reveals alterations of the integrative autonomic control of circulation in paraplegic individuals. (27th April 2017) - Castiglioni, Paolo; Merati, Giampiero
Abstract: The autonomic nervous system plays a major role in the integrative control of circulation, possibly contributing to the 'complex' dynamics responsible for fractal components in heart rate variability. Aim of this study is to evaluate whether an altered autonomic integrative control is identified by fractal analysis of heart rate variability. We enrolled 14 spinal cord injured individuals with complete lesion between the 5th and 11th thoracic vertebra (SCIH ), 14 with complete lesion between 12th thoracic and 5th lumbar vertebra (SCIL ), and 34 able-bodied controls (AB). These paraplegic subjects have an altered autonomic integrative regulation, but intact autonomic cardiac control and, as to SCIL individuals, intact autonomic splanchnic control. Power spectral and fractal analysis (temporal spectrum of scale coefficients) were performed on 10 min tachograms. AB and SCIL power spectra were similar, while the SCIL fractal spectrum had higher coefficients between 12 and 48 s. SCIH individuals had lower power than controls at 0.1 Hz; their fractal spectrum was morphologically different, diverging from that of controls at the largest scales (120 s). Therefore, when the lesion compromises the autonomic control of lower districts, fractal analysis reveals alterations undetected by power spectral analysis of heart rate variability.